Poor Prognosis of Grade 2 Spread Through Air Spaces in Neuroendocrine Tumors - Mincheol Chae; Sukki Cho; Jin-Haeng Chung; Sungwon Yum; Kwhanmien Kim; Sanghoon Jheon (Journal of Chest Surgery, 2022)
Background: Spread through air spaces (STAS) has recently emerged as a prognostic factor in lung adenocarcinoma, but little is known about the association of STAS and its grade with recurrence in neuroendocrine tumors (NETs). This study investigated the prognostic effect of STAS grade in NETs after curative resection. Methods: Seventy-seven patients were retrospectively reviewed, including 9 with typical carcinoid (TC), 6 with atypical carcinoid (AC), 26 with large cell neuroendocrine carcinoma (LCNEC), and 36 with small cell carcinoma (SCC). STAS was defined as the presence of floating tumor cells within air spaces in the lung parenchyma beyond the edge of the main tumor. STAS was classified as grade 1 or 2 depending on whether it was found within or beyond one ×10 objective lens field away from the main tumor margin, respectively. Results: Fifty-four patients (70%) had STAS, including 22% with TC, 50% with AC, 69% with LCNEC, and 86% with SCC. Patients with STAS had more nodal metastasis, lymphatic and vascular invasion, tumor necrosis, and tumor subtypes other than TC. Among STAS cases, grade 2 STAS was present in 33% of AC, 78% of LCNEC, and 87% of SCC. The 5-year recurrence-free survival (RFS) rate was 81%, 63%, and 35% in patients with no STAS, grade 1, and grade 2 STAS, respectively. Multivariate analysis found that grade 2 STAS was an independent negative prognostic factor for RFS. Conclusion: Although STAS itself was not associated with a poor prognosis, grade 2 STAS was an independent negative prognostic factor for RFS.